Demographic Inequalities in Using E-Banking Services: A Study of Chandigarh - Khosla, Rajiv; Munjal, Parul (Indian Journal of Finance, 2013)
The Indian banking system has undergone a sea change since liberalization. Conservative-banking in the past has given way to a highly progressive system of modern banking. Besides providing basic banking services, today's banks provide a plethora of services like ATM/Debit cards, Credit cards, Internet banking, M - banking, etc. Such radical changes are brought on to the surface by Internet banking commonly known as e-banking. Despite this, many customers are hesitant to use e-banking in India. This study is an attempt to understand the importance of various determinants that act as stimulants in guiding different segment of customers to use e-banking services.